Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Dan Motivasi Belajar Siswa Di Kelas V Sekolah Dasar - Riska Nanda Putri; Melva Zainil; Desyandri; Yeni Karneli (Postgraduate, University of Mataram, 2025)
Students have not been actively involved in finding their own concepts or learning materials. One effort that can be made is to use the Problem Based Learning model. This study aims to determine the effect of the Problem Based Learning model on students' problem-solving ability and learning motivation in Mathematics learning in Grade V of Elementary School. The type of research used is Quasi Experimental. The sample of this study was class Va students as the experimental class and class VB students as the control class. While to test the hypothesis using the independent t test. To determine the relationship between problem-solving ability and learning motivation, a correlation test was carried out. The results of this study indicate that there is an effect of the Problem Based Learning model on students' problem-solving ability and learning motivation in Mathematics learning in Grade V of Elementary School. Details of the data analysis results are: The results of the independent t test on problem-solving ability obtained a significant value of 0.761 for the pretest and 0.000 for the posttest. By taking a significance value of 5%, it is concluded that the Ha of this study is accepted, while H1 is rejected, meaning that there is an influence of the Problem Based Learning learning model on students' problem-solving ability in Mathematics learning; The results of the independent t test on learning motivation obtained a significance value of 0.588 for the pretest and 0.000 for the posttest.